Simulation model algorithm for pre-hospital emergency care (PHEC) volunteers in Indonesia - Martono, Martono; Sudiro, Sudiro; Satino, Satino (Penerbit Universiti Kebangsaan Malaysia, 2018)
The first responders who are often exposed to emergency condition play important roles in providing PHEC to victims with road accident trauma. Hence, empowerment of first responders is highly required to achieve the target of response time of less than 10 minutes to provide PHEC in order to minimize the numbers of deaths and disabilities caused by trauma. This study applied quasi-experimental design with static group comparison pattern using cross-sectional approach. A number of 40 samples of common people consisting of 20 samples in treatment group and 20 samples in control group were taken. The statistic test used in this research is t-test. The results reveals that simulation model using algorithm influences the improvement of traffic volunteers’ emergency management capabilities with p-value of < 0.05 and mean score difference of 34.5%, and the model is highly effective to be implemented to improve the capability of traffic assistant volunteers to manage trauma emergency with the mean score difference of 11.5%. Algorithm models for PHEC simulation have some strengths in real setting and effective interactive learning to evaluate the capabilities of first responders in managing pre-hospital emergency, and improve problem-solving skills, as well as their performance in such aspects as skill, knowledge, and attitude.